Nonlinear finite element analysis of steel fiber reinforced concrete beams subjected to impact loads - Serdar, Ahmet Hamdi; Caglar, Naci; Demirtas, Gamze; Saribiyik, Mehmet (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2024)
Steel fiber reinforced concrete, compared to the conventional concrete; is a composite building material that performs much better in terms of parameters such as ductility, energy absorption capacity, fracture toughness, fatigue resistance, and the use of steel fiber reinforced concrete (SFRC) in structures has become widespread. In this study, a nonlinear finite element model (FEM) has been developed that can represent the behavior of beams produced by using steel fiber concrete subjected to impact load. For this purpose, a finite element model of beam series produced with fiberreinforced concrete obtained from the literature was created. The ABAQUS package program was used to create models simulating the behavior. Numerical results showed that the model could successfully capture the experimental results of beams selected from the literature. In addition to simulation, a parametric study was also performed to investigate the effect of stirrups, reinforcement ratio, and drop height on the behavior of SFRC beams under impact loads. The results of the parametric study showed that increasing the fiber ratio and reinforcement ratio positively affected the behavior of SFRC beams in terms of displacement recovery.
Keywords: steel fiber reinforced concrete; RC beam; impact load; nonlinear finite element analysis